Comparing and Change : Orders, Models, Perceptions - Flüchter, Antje (2024)
Comparisons affect various ways of perceiving and interpreting the world, characterized by distinct legitimization strategies and knowledge application routines by different actors. The contributors to this volume explore the link between change and practices of comparing, focusing on order, representation, and models. They delve into how comparing influences knowledge production, but also focus on persisting orders of knowledge. This collection centers on the role of models and modeling in relation to practices of comparing, thus highlighting the representational and operational force of comparing as a way to form and organize reality.